MALPRAKTIK OLEH TENAGA KEPERAWATAN DI FASILITAS KESEHATAN PRIMER: URGENSI PENGUATAN SISTEM PENGAWASAN DAN PERLINDUNGAN HUKUM PASIEN - Sartono Sartono; Sandy Marzuqi Rahmat; Gemah Arfiyah; Ahmad Ma’mun Fikri (Universitas Labuhanbatu, 2025)
This study aims to provide a comprehensive legal understanding of nurses’ liability in malpractice cases at primary healthcare facilities. Using a normative legal approach and analyzing laws such as Law No. 38 of 2014 on Nursing and Law No. 36 of 2014 on Health Workers, it finds that nurses are authorized to provide care only within their competencies. Violations may lead to criminal, civil, or administrative liability. The study also reveals weak delegation of authority and institutional oversight, contributing to malpractice risks. Strengthening responsive regulations and preventive, continuous supervision is urgently needed. The findings are expected to inform policymakers and professional organizations in enhancing patient legal protection and clarifying the scope of nursing responsibilities. Keywords: Nursing Malpractice; Primary Healthcare Facilities; Oversight System; Legal Protection For Patients